The fetal-maternal interface of the nine-banded armadillo: endothelial cells of maternal sinus are partially replaced by trophoblast. Issue 1 (December 2016) - Chavan, Arun; Wagner, Günter
Abstract Background The evolution of invasive placentation in the stem lineage of eutherian mammals entailed resolution of the incompatibility between a semi-allogenic fetus and the maternal immune system. The haemochorial placenta of nine-banded armadillo (Dasypus novemcinctus ) is thought to conceal itself from the maternal immune system to some degree by developing inside a preformed blood sinus, with minimal contact with the uterine connective tissue. In the present study, we elucidate the micro-anatomical relationship between fetal and maternal tissue of the nine-banded armadillo using histochemical and immunohistochemical tools. Results We conclude that the chorio-allantoic villi are separated from the myometrium by a vascular endothelial layer, as previously proposed. However, we also observe that the trophoblast cells establish direct contact with the endometrial stroma on the luminal side of the endometrium by partially replacing the endothelial lining of the sinus. Further, we demonstrate the presence of leukocytes, perhaps entrapped, in the placental fibrinoids at the interface between the intervillous space and the endometrial arcade. Conclusions The trophoblast of the armadillo invades the uterine tissue to a greater extent than was previously believed. We discuss the implications of this finding for the fetal-maternal immune tolerance.